Identification of modal properties of a steel footbridge using ambient vibration measurement - Paguirigan, Janford E.
Identification of modal properties is essential in evaluation of structural safety. However, such properties of structures can only be fully assessed after construction. Thus, ambient vibration testing is performed as it is one of the most commonly used field vibration measurement for big structures because it is non-destructive, economical, and fast and easy to implement. Sources of ambient excitation include wind, microseisms and pedestrian activities. In this study, the modal properties of the steel footbridge across AIT and CHK in UP Diliman, Quezon City was identified using ambient vibration measurement. Field measurement, for two setups, started with the simultaneous recording of the structure's response from the installed 20 accelerometer. After validation of the data acquired, the Peak Picking Method (PP), Frequency Domain Decomposition (FDD), and Stochastic Subspace Identification (SSI) were used to extract the natural frequencies, damping ratios and mode shapes of the footbridge. From the both setups, six identified modes from FDD and SSI were compared. The estimated natural frequencies ranged from 1.92 Hz to 13.98 Hz. Then, it was found out that the modal properties obtained from FDD are in good agreement with the result of SSL.